2019
DOI: 10.1080/13607863.2019.1697201
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of older adults’ request for or attitude toward euthanasia or assisted-suicide

Abstract: Objectives: Prevalence rates of death by euthanasia (EUT) and physician-assisted suicide (PAS) have considerably increased in older adults, and public debates on these practices are still taking place. In this context, it seemed important to conduct a systematic review of the predictors (demographic, physical, psychological, social, quality of life, religious or existential) associated with attitudes toward, wishes and requests for, as well as death by EUT/PAS among individuals aged 60 years and over. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
39
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 59 publications
(136 reference statements)
11
39
3
Order By: Relevance
“…Analysis of responses of 1066 individuals in the US General Social Survey found that religiosity, belief in the afterlife and heaven, and religious denomination were significantly associated with opposition to euthanasia (Sabriseilabi & Williams, 2020). Finally, a review of the literature by Castelli Dransart et al (2019) reported that religious affiliation was not associated with support for euthanasia or physician-assisted suicide in Switzerland or Connecticut, and Indiana in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of responses of 1066 individuals in the US General Social Survey found that religiosity, belief in the afterlife and heaven, and religious denomination were significantly associated with opposition to euthanasia (Sabriseilabi & Williams, 2020). Finally, a review of the literature by Castelli Dransart et al (2019) reported that religious affiliation was not associated with support for euthanasia or physician-assisted suicide in Switzerland or Connecticut, and Indiana in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Among these constructs are several established risk factors for suicide-related outcomes, including depression, anxiety, posttraumatic stress disorder (PTSD), hopelessness, fear, unresolved anger, guilt, worthlessness, sleep problems, self-stigmatization, feelings of entrapment and burdensomeness, substance misuse, loneliness, social isolation, disconnectedness, disruption of everyday routines, unemployment, financial strain/insecurity, domestic violence, and child neglect/abuse (Cullen et al, 2020;Dong & Bouey, 2020;James et al, 2019;Jeste et al, 2020;Oyesanya et al, 2015;Reger et al, 2020). Since many of these factors are also associated with accessing medical assistance in dying (MAID; Castelli Dransart et al, 2019) it remains to be seen whether epidemics led to increases in MAID as well. Exploration of the psychiatric and neuropsychiatric presentations associated with severe coronavirus infections (Rogers et al, 2020;Tucci et al, 2017) highlights the frequent occurrence of delirium/confusion in the acute phase, and higher levels of depression, fatigue, insomnia, anxiety, and PTSD in the postacute phase.…”
Section: Pathways From Public Health Emergencies To Suicide-related Outcomesmentioning
confidence: 99%
“…With EU, the physician administers lethal medications to patients in order to relieve their suffering by bringing about their death; while with PAS, the physician usually provides the lethal substances, but the patients have to end their own life (Gerson et al, 2020). EU and PAS are legally practiced in 15 regions of the world, mostly in Western countries like Canada (Castelli Dransart et al, 2019). Issues, such as grievous incurable illnesses, or advanced state of irreversible decline (Beuthin, 2018), which cause unbearable physical and psychological suffering, were common justifications for their legalization in these countries (Castro et al, 2016).…”
mentioning
confidence: 99%
“…Many factors influence the position towards EU and PAS. Younger age, being divorced or widowed, living alone, and higher education and income, were associated with a favorable attitude towards EU or PAS in older adults (Castelli Dransart et al, 2019). Ageist societal discourse about the increasing burden and cost of the elderly population, as well as the perception to be no longer a useful or valuable member of the society increase the likelihood that older adults would choose a hastened death in a hypothetical terminal illness situation (Castelli Dransart et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation